2011
DOI: 10.1002/jnr.22624
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal changes in promoter activity of the astrocyte glutamate transporter GLT1 following traumatic spinal cord injury

Abstract: After traumatic spinal cord injury (SCI), there is an opportunity for preserving function by attenuating secondary cell loss. Astrocytes play crucial roles in the adult CNS and are responsible for the vast majority of glutamate buffering, potentially preventing excitotoxic loss of neurons and oligodendrocytes. We examined spatial and temporal changes in gene expression of the major astrocyte glutamate transporter GLT1 following moderate thoracic contusion SCI using transgenic BAC-GLT1-eGFP promoter reporter mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
34
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 49 publications
6
34
0
1
Order By: Relevance
“…In addition, the spatial heterogeneity of reactive astrocytes is also observed following CNS injury (Lepore et al 2011;Rusnakova et al 2013). After acute injury, live imaging of cerebral cortex revealed a marked heterogeneity in the reaction of individual astrocytes, with one subpopulation retaining their initial morphology, another directing their processes toward the lesion, and a distinct subpopulation located at juxtavascular sites proliferating (Bardehle et al 2013).…”
Section: Traumatic Injurymentioning
confidence: 96%
“…In addition, the spatial heterogeneity of reactive astrocytes is also observed following CNS injury (Lepore et al 2011;Rusnakova et al 2013). After acute injury, live imaging of cerebral cortex revealed a marked heterogeneity in the reaction of individual astrocytes, with one subpopulation retaining their initial morphology, another directing their processes toward the lesion, and a distinct subpopulation located at juxtavascular sites proliferating (Bardehle et al 2013).…”
Section: Traumatic Injurymentioning
confidence: 96%
“…Transplantation also provides for long-term astrocyte integration and therapeutic replacement. For example, the lasting nature of dysregulation of extracellular glutamate homeostasis after SCI (Lepore et al, 2011a; Lepore et al, 2011c) calls for longer-term maintenance of therapeutic effects, both with respect to early cell loss occurring during secondary degeneration and outcomes of SCI associated with more persistent pathophysiology of glutamate signaling such as chronic neuropathic pain (Gwak et al, 2012; Hulsebosch, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, we and others demonstrated that astrocyte GLT1 was chronically lost at the injury epicenter following SCI but also downregulated in spinal cord regions distant from the lesion core [103][104][105][106] . Furthermore, experimental data showed that the newlygenerated astrocytes arising during the SCI repair phase lacked GLT1 expression, possibly compromising long-term astrocyte glutamate homeostasis [107] . Other consequences of astrocyte dysfunction or loss should be considered in ALS and SCI: shortage of neurotrophic factors important for neuronal survival, overwhelming of anti-oxidative defenses, lack of support to maintain endothelial BBB integrity, impaired water, ionic and metabolic transport, release of harmful proinflammatory cytokines and synthesis of glial scar-related ECM proteins that block axonal regrowth [1] .…”
mentioning
confidence: 99%